Dielectric measurement techniques of biological tissue: A review on electrodes perspective - Ruzairi, Abdul Rahim, Prof. Dr.; Zulkarnay, Zakaria; Maliki, Ibrahim; Muhammad Saiful Badri, Mansor; Siti Zarina, Mohd. Muji, Dr.; Nor Muzakkir, Nor Ayub (International Frequency Sensor Association Publishing (IFSA), 2013)
Link to publisher's homepage at http://www.sensorsportal.com/